Guidelines to Operate Internal Quality Assurance of the Basic Education Institutions underNakhon Ratchasima Primary Educational ServiceArea Office 7 - ซื่อสัตย, รัตนา; หกสุวรรณ, สุทธิพงศ์ (Journal of Roi Et Rajabhat University, 2016)
The purposes of this study were to: 1) study current and desirable study current and desirableconditions of internal quality assurance operations of basic education quality assurance operations of basic education institutions institutions under Nakhon Ratchasima Primary Educational Service Area Office 7, Educational Service Area Office 7, and 2) establish guidelines guidelines for internal quality assurance operations operations of basic education institutions under Nakhon Ratchasima Primary Educational Service Area Office 7. The sample in this research divided into two groups. Group one consisted of responsible people for school internal quality assurance in education included school administrators, responsible teachers for school internal quality assurance in education, and teachers at schools under Nakhon Ratchasima Primary Educational Service Area Office 7 in an academic year BE 2557. The research sample included 335 people and used multi–stage random sampling. Group two were major contributors included 6 luminaries, 5 executives and 6 teachers. Research instruments were a five– rating scale questionnaire and an interview form. The data was analyzed by using mean and standard deviation. Modified Priority Needs Index (PNI Modified) was used to arrange the expectations. The results found that; 1. The current and desirable conditions of internal quality assurance operation of basic education institutions under Nakhon Ratchasima primary educational service area office 7 overall were performed in a very good level. 2. The overview guidelines of internal quality assurance operations of basic education institutions under Nakhon Ratchasima primary educational service area office 7 were schools should; 1) provide the meeting to plan and set educational standard for the school by the acceptance of all parties involved, 2) prepare a school development plan to meet quality of educational standard of the school requires a strategic analysis by using SWOT Analysis. The analysis of strengths, weaknesses, opportunities, and threats need to be all around to establish the school development plan, 3) establish of administration and information system should provide a school management structure or school management systems to support the development system of school internal quality assurance, 4) operate schools based on the school development plan, school administrators should provide sufficient facilities and resources for personal needs appropriately, 5) provide a regulating and monitoring calendar and prepare the hand book for internal assurance. 6) provide internal quality assurance as school educational standard should have a workshop to improve knowledge and skills about internal quality assurance based on educational standards and indicators, 7) prepare an annual report about internal quality assurance, schools should appoint to a working committee which consists of personnel from all departments. This will make all personnel recognize and use information for the assessment based on indicators of standard of education and 8) provide educational development continually, schools should improve educational development patterns to suit to school contexts.